Kesinambungan dan Perubahan Tradisi Salaf dalam Sistem Pendidikan Pondok Pesantren Lirboyo Kediri - Kadi Kadi (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2017)
This article answers the problem of continuity and change of salaf tradition in the educational system of Pondok Pesantren Lirboyo Kediri. Using system theory along with historical, sociological, anthropological and phenomenology-cal appraoch, this article reveals some important points. First, the salaf tradition of pesantren undergoes substantial continuity, where knowledge structure of pesantren are conserved in learning of religious sciences originated from classical books, and partial change, where changes occur in the aspect of learning method, curriculum development, and teachers from outside pesantren. Second, there are internal and external factors that drive continuity and change in salaf tradition in the educational system of Pesantren Lirboyo. The internal factor is the attitude and thought of kiai as the servant of ummah (khÄdim al-ummah) and the objective condition of santri. While the external factor occurs because the development of the system of public education and the development of science and technology.